Integrating powerpoint as an instructional medium to enhance science learning performance in junior secondary education - Ab, Darlis (Science Center Group, 2025)
Background: The integration of digital instructional media has become increasingly essential in improving students’ academic performance, particularly in science education at the junior secondary level. Structured visual presentation tools such as PowerPoint offer systematic content organization, interactive features, and guided conceptual explanation that may enhance students’ cognitive achievement. Objective: This study aimed to determine the effectiveness of integrating PowerPoint as an instructional medium to enhance science learning performance among junior secondary students. Methods: A quasi-experimental design employing a pre-test–post-test control group approach was conducted with two intact classes consisting of 60 students. The experimental group received science instruction supported by structured and interactive PowerPoint presentations, while the control group received conventional instruction without digital media integration. Data were collected using a validated cognitive achievement test and analyzed through descriptive statistics, independent and paired samples t-tests, and normalized gain (N-Gain) analysis to measure learning improvement. Results: The findings revealed that the experimental group achieved significantly higher post-test scores compared to the control group (p < 0.05). The mean N-Gain score of the experimental group (0.59) indicated moderate-to-high effectiveness, whereas the control group demonstrated moderate effectiveness (0.31). These results confirm that structured PowerPoint integration significantly enhances students’ science learning performance. Conclusion: The study concludes that integrating PowerPoint as a structured instructional medium effectively improves cognitive achievement in junior secondary science education. The findings provide empirical support for the systematic incorporation of interactive presentation media to strengthen science learning outcomes.